2019
DOI: 10.4314/ijs.v21i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of mango (<i>Mangifera indica</i> L.) cultivars from south-west Nigeria

Abstract: Mango (Mangifera indica L.) is an economically important tropical fruit consumed all over the world. So far, little attention has been paid towards the documentation and characterization of its cultivars. Occupying a unique position among edible fruit crops in Nigeria, information on the exact number of cultivars has not been recorded, leading to a lack of accurately named germplasms and cultivars. To gain phenomenal insight on cultivars' diversity, a morphological technique employing both cluster and principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The leaves characters are spirally arranged on branches, lanceolate-elliptical, pointed at both ends and borne on 1-12.5 cm long petioles. Leaves are mostly about 16-30 cm long and 3-8 cm wide on flowering branches, and up to 50cm long on sterile branches (Shah et al 2010;Igbari et al 2019). So, the values of morphological analysis for mango leaves of all the nineteen different cultivars depicted in Table 2 fitted perfectly with the ranges mentioned above.…”
Section: Discussionsupporting
confidence: 58%
“…The leaves characters are spirally arranged on branches, lanceolate-elliptical, pointed at both ends and borne on 1-12.5 cm long petioles. Leaves are mostly about 16-30 cm long and 3-8 cm wide on flowering branches, and up to 50cm long on sterile branches (Shah et al 2010;Igbari et al 2019). So, the values of morphological analysis for mango leaves of all the nineteen different cultivars depicted in Table 2 fitted perfectly with the ranges mentioned above.…”
Section: Discussionsupporting
confidence: 58%
“…The Sensation mango cultivars recorded the lowest values of fruit length, width, total fruit weight, pulp weight, and pulp percentage (Hussein and Ali, 2019). The highest average of the total reducing and nonreducing sugars was reported in the fruit of mango cultivar Glenn, while mango cultivar Kent showed a fruit length of 13.2 cm, a fruit width of 10.3 cm, with green fruit color (Igbari et al, 2019). The variation among the cultivars revealed in fruit size, fruit shape index, fruit pulp firmness, pulp and seeds (%), and fibers (%) per fruit might be due to the differences in the mango genotypes and agro-climatic conditions and the inherent variation in the absorption and translocation of photosynthates and plant hormones.…”
Section: Discussionmentioning
confidence: 94%
“…In this case PCA has important role in identifying morphological variation patterns [23] and in determining the relative contribution of characters to the variations found in samples under study [3]. Due to its complementary role, PCA was commonly used in conjunction with cluster analysis in taxonomic studies at family, genus, and species level such as those reported on Amaranthaceae [33], Abelmoschus [34], and Mangifera indica [35]. Accordingly, combination of these two multivariate analysis methods, the cluster analysis and PCA, has also been applied widely in sorghum diversity studies [12,27,28,36,37].…”
Section: Resultsmentioning
confidence: 99%